REVIEW ON EVALUATION OF FROZEN SHOULDER IN PEOPLE WITHDIABETES - Layla Abd-Al-Sattar Sadiq Laylani (Scholar Express Journals, 2023)
You may get a clinical diagnosis of frozen shoulder, which is a painful and debilitating illness. Classical clinical indications include painful restriction of shoulder motion due to persistent inflammation and proliferative fibrosis. Those with diabetes are at increased risk for developing the condition and may need surgical treatment more often. The practitioner managing diabetic frozen shoulder must find a middle ground between increasing the patients range of motion and alleviating discomfort and overtreating a disease that often resolves on its own. Physiotherapy and intra-articular injections are the mainstays of treatment, with hydro dilatation, anesthetic manipulation, and arthroscopic capsular release as potential next steps. In this study, we propose a care plan for treating patients with diabetic frozen shoulder based on a review of the current literature and correlation with experience at our hospital. Decisions on the patient's care should be made in collaboration with the patient, taking into account co-morbidities, severity, and the condition's natural history
Keywords: Management; Adhesive capsulitis; Frozen shoulder